Democratic Agnosia: The Reduction of the Political Public Sphere to Elections and Polls in Russia - Langenohl, Andreas; Schmäing, Sophie (Javnost-The Public, 2020)
The article addresses the extent to which current developments in the political public sphere in contemporary Russia might be seen as manifestations and maybe condensations of developments in representative democracies in a more general sense. These developments concern the ways that elections and other practices of voting achieve a hegemonic significance as processes of symbolization in the political public sphere. The first section outlines the role of voting practices for the legitimation and stability of Russia’s current super-presidentialism. The second section connects these findings to a theoretical framework that capitalizes on the symbolic effects of elections and polling practices in democratic political and societal orders. Here critics of representative democracy and of majority rule, which highlight the contradictory role of majority decisions in democratic institutional and imaginary orders, will be discussed and related to the mass protests against election fraud in 2011 and 2012. The third section reconceptualizes the current problematics of the political public sphere in contemporary Russia. The overall aim is thus not to measure political-public developments in Russia against the normative yardstick of allegedly uncontested democratic development in western societies, but rather to situate Russia on a conceptual map of a generic crisis of majority rule.